The impact of Arkoun’s life on his vision of the religious text or the sacred - boualem, samir (Journal of Social Sciences and Humanities, 2025)
From within the Arkounian House, and its narrow dogmatic arenas, the new critical plant is born out of the walls of the thinker and its unscientific ideological nature. It is the begining of the reality of criticism, re-reading, and embedding the accountability that opens the horizon wide for Arab and Islamic. Arkoun’s genius to open prohibited paradigms makes the content of this artrical betting primarily on revealing the deep soul entrances to Arkoun’s eagerness to liberate from the stigma of the self and its oneness sensing the new that will serve as a comprehensive review of the various dominant historical sites that will establish cultural traditions from criticism outside of the epistemological implications of traditional throught and open to the gains and developments of the humanities sciences that will restore the problems of Arab-Islamic life from the standpoint of the western cultural norm. From this particular ground, and from the depths of the Arkounian life that rejects the idea of alienation and ditching in any way within the network of the forbidden sacred thought, the life of Arkounin its entire phases and stations will have a significant and fundamental impact on his vision of the religious or sacred text, which will end up in a secular rather than religious dominated by human centralism.